2005
DOI: 10.9749/jin.112.345
|View full text |Cite
|
Sign up to set email alerts
|

Mooring Limit of Small Fishing Boat at Kumaishi Fishing Port

Abstract: Recentiy , port distUrbance and 皿 oo 血 g distUrbance caused by oscillation has been seen as a problem at many 卿 s and bo雌 , and fishing pomS , The 舳 。rs clarified the mechanism of port disturbance generation at Kumaishi fishing po鶏 based on field observa 匠on and numerical simulati . Howeve ろ tl } e limit wave height which cause moor disturbance on small fishing boats has not been clarified . The autho 埒 have analyzed moo 血 g limit fbcusing on lo 一 period wave heig 瓧s based on past disasters exempla and the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Additionally, the storm surge can be influenced significantly by the landfall location of a typhoon with the same pressure (Sun et al, 2015). Abeshima et al (2017) clarified the mechanism of port disturbance generation at the Kumaishi fishery port and concluded that the quantitative indicator H 1/3 (over 2.0 m) can be introduced as a decision indicator for evacuations by observational statistics. Some exploratory work has been conducted in China on fishery ports' resistance to damage caused by typhoons.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the storm surge can be influenced significantly by the landfall location of a typhoon with the same pressure (Sun et al, 2015). Abeshima et al (2017) clarified the mechanism of port disturbance generation at the Kumaishi fishery port and concluded that the quantitative indicator H 1/3 (over 2.0 m) can be introduced as a decision indicator for evacuations by observational statistics. Some exploratory work has been conducted in China on fishery ports' resistance to damage caused by typhoons.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the storm surge can be influenced significantly by the landfall location of a typhoon with the same pressure (Sun et al, 2015). Abeshima et al (2017) clarified the mechanism of port disturbance generation at the Kumaishi fishery port and concluded that the quantitative indicator H1/3 (over 2.0 m) can be introduced as a decision indicator for evacuations by observational statistics. Some exploratory work has been conducted in China on fishery ports' resistance to damage caused by typhoons.…”
mentioning
confidence: 99%